2016
DOI: 10.18632/oncotarget.9895
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor beta reduces colon cancer metastasis through a novel miR-205 - PROX1 mechanism

Abstract: Colon cancer is a common cause of cancer death in the Western world. Accumulating evidence supports a protective role of estrogen via estrogen receptor beta (ERβ) but the mechanism of action is not known. Here, we elucidate a molecular mechanism whereby ERβ represses the oncogenic prospero homebox 1 (PROX1) through the upregulation of miR-205. We show that PROX1 is a potential target of miR-205 and that in clinical specimens from The Cancer Genome Atlas data, ERβ and miR-205 are decreased in colorectal cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 38 publications
3
37
1
1
Order By: Relevance
“…Overexpression of PROX1 has been shown to enhance colon cancer progression in vivo ; indeed, it has been associated with transition from benign adenoma to carcinoma, and silencing of this transcription factor inhibits the growth of human colorectal tumor xenografts [91]. We have demonstrated that PROX1 is repressed by ERβ, through the regulation of microRNA miR-205, and results in a repression of metastatic potential of CRC cells [92]. This pathway was confirmed in clinical specimens and could be recapitulated in intestine-specific ERβ knockout mice [92].…”
Section: The Molecular Mechanism Of Action Of Erβ In Colon Epithelmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of PROX1 has been shown to enhance colon cancer progression in vivo ; indeed, it has been associated with transition from benign adenoma to carcinoma, and silencing of this transcription factor inhibits the growth of human colorectal tumor xenografts [91]. We have demonstrated that PROX1 is repressed by ERβ, through the regulation of microRNA miR-205, and results in a repression of metastatic potential of CRC cells [92]. This pathway was confirmed in clinical specimens and could be recapitulated in intestine-specific ERβ knockout mice [92].…”
Section: The Molecular Mechanism Of Action Of Erβ In Colon Epithelmentioning
confidence: 99%
“…We have demonstrated that PROX1 is repressed by ERβ, through the regulation of microRNA miR-205, and results in a repression of metastatic potential of CRC cells [92]. This pathway was confirmed in clinical specimens and could be recapitulated in intestine-specific ERβ knockout mice [92]. In summary, a number of studies support that the molecular mechanism whereby ERβ protects against tumorigenesis by enhancing DNA repair and apoptosis while repressing oncogene expression, proliferation and metastasis (Figure 1).…”
Section: The Molecular Mechanism Of Action Of Erβ In Colon Epithelmentioning
confidence: 99%
“…Further, estrogen through estrogen receptor β (ERβ/ESR2) appears to reduce the risk of CRC development (reviewed in []). Our previous cell‐based analyses have shown that re‐introduction of ERβ into CRC cells exhibits anti‐proliferative functions, represses oncogenes, and mediates anti‐inflammatory signaling . Studies in mice have generated support in vivo for such a preventive role .…”
Section: Introductionmentioning
confidence: 99%
“…However, whether intestinal ERβ affects the microbiota of the gut has not been investigated. To explore the effect of ERβ in the intestines, we have generated intestine‐specific knockout of ERβ (referred to as ERβKO Vil or simply KO in the remainder of the text) . Here, we characterize how the microbiota composition is affected by AOM/DSS‐driven colitis and CRC development in mice with and without intestinal ERβ.…”
Section: Introductionmentioning
confidence: 99%
“…While they found high miR205 expression in non-metastatic tissue, miR205 was absent in metastatic tissue [29]. Furthermore, over-expression of miR205 resulted in reduced invasiveness and metastatic potential in prostate and colon cancer cells [30,31]. Regarding BTC, a study by Okamoto et al demonstrated that over-expression of miR205 enhanced sensitivity to the standard chemotherapeutic Gemcitabine, which, again, categorizes miR205 as a tumor suppressor miR in this particular case [32].…”
Section: Discussionmentioning
confidence: 99%